Pengaruh Waktu Reaksi Dan Rasio Molar Terhadap Asam Oleat Dengan Butanol Pada Sintesa Plastisizer Butil Oleat - Selly, Mers; Nirwana, Nirwana; HS, Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The amount of palm oil feedstock in Indonesia, encourages the development of palm oil industry product diversification. One alternative for providing value-added palm oil by esterification of oleic acid is contained in palm oil became known as butyl oleate plasticizers. Plasticizer is an additive compound added to polymer to improve flexibility and workabilitas. Step of this research is the preparation of H-zeolite catalysts and synthesis of the plasticizer butyl oleate esterification using natural zeolite catalysts are activated to H-zeolites with varying reaction time (6, 9 and 12 hours) and the molar ratio of oleic acid and butanol (1: 6 , 1: 9 and 1:12) with the permanent variable stirring speed of 200 rpm, temperature of 108-112 ° C and catalyst-based as much as 15% oleic acid. From the test results showed that the reaction time and the molar ratio of the plasticizer effect on the synthesis of butyl oleate. Obtained value of 0.862 specific gravity and viscosity of 8.39 mPa by showing that the specific gravity and viscosity plasticizer produced meets the standards of commercial plasitisizer namely 0.862 to 0.928 and from 8.2 to 9.4. The highest achievement in this research was 76.73% with a molar ratio of 1:12 for 12 hours process.Keywords: Esterification, H-zeolites, Oils, Plasticizers